Soil microclimate and vegetation dynamics shape elevational and seasonal variations of diazotrophic communities in alpine grasslands - Rui, Junpeng; Long, Xiaojian; Wang, Xuemiao; Xiong, Xinyu; Zhu, Jianxiao (Frontiers in Plant Science, 2025)
IntroductionDiazotrophs play critical roles in maintaining ecosystem nitrogen (N) cycling in alpine grasslands. However, the elevational and seasonal variations of diazotrophic communities in these ecosystems remain poorly understood. This gap in knowledge limits our ability to predict how N fixation will respond to environmental change. Here, we investigated the seasonal dynamics of soil diazotrophic communities across a 3200-4000 m elevational gradient in Qinghai-Tibetan alpine grasslands during the growing season.MethodsSoil samples were collected across an elevational gradient (3200-4000 m) throughout the growing season. The diazotrophic community composition was assessed by sequencing the nifH gene, which was also quantified using quantitative PCR. Soil nitrogenase activity was measured to assess N fixation potential. Key environmental variables, such as soil temperature, moisture, and plant biomass (particularly legume biomass), were monitored.Results and DiscussionOur results revealed that diazotrophic alpha-diversity followed an inverted V-shaped pattern along the elevational gradient, primarily driven by soil temperature and moisture. Beta-diversity analyses demonstrated that diazotrophic communities generally exhibited similar elevational distribution patterns throughout the growing season, also primarily influenced by temperature and moisture. Seasonal variations in diazotrophic communities were more pronounced at lower elevations, primarily associated with plant biomass dynamics, including delayed legume emergence at 3200 m in June and their subsequent biomass accumulation after July. In contrast, soil microclimate (particularly temperature) dominated community shifts at higher elevations. Notably, nifH gene abundance and soil nitrogenase activity were higher in the early growing season, suggesting free-living diazotrophs may play a crucial role in N fixation. Abundant species were key contributors to diazotrophic beta-diversity. Symbiotic Mesorhizobium was more abundant at low elevations, while free-living Geobacter at high elevations. Conversely, associative diazotrophs peaked later in the growing season, in contrast to Geobacter. Rare species played a key role in shaping alpha diversity, particularly at mid-elevations, where soil moisture was the highest. Our study underscores the complex interactions between soil microclimate change and plant dynamics in regulating diazotrophic communities. Furthermore, it highlights the essential roles of both abundant and rare species in sustaining ecosystem functions in alpine grasslands. These findings provide new insights into the biogeochemical processes supporting N cycling in alpine grasslands and highlight the potential impacts of vegetation and climate change on these fragile ecosystems.